Factors associated with return to work in patients with long-term disabilities due to neurological and neuropsychiatric disorders. Issue 9 (21st October 2019) - Mitrushina, Maura; Tomaszewski, Robert
ABSTRACT: The current study explores factors predicting return to work in a sample of patients with neurological and neuropsychiatric disorders who have attended a prevocational readiness and social skills training programme many years after trauma. Participants were community-dwelling adults with long-term disabilities ( N = 67). Results of univariate analyses followed by multivariate logistic regression analysis revealed that both pre-injury (prior) and post-injury (current) factors influenced the likelihood of employment in our sample: prior employment, current employment readiness, current cognitive competence (particularly memory and executive functioning) and emotional adjustment. Our findings demonstrate that both pre-trauma and current factors interact in predicting return to work not only for individuals with traumatic brain injury (TBI), but also for a broader group of patients with long-term disabilities due to a variety of neurological and neuropsychiatric conditions. Thus, our findings provide preliminary support for ongoing long-term management of individuals with long-term disabilities and warrant close attention of future investigators to potential benefits of cognitive remediation, psychotherapy and vocational rehabilitation in terms of maintenance of initial gains and increased probability of return to work many years after trauma.